Production of four cultivars of iceberg lettuce, under protected cultivation, with and without black polyethylene ground cover - Castoldi, R. [UNESP]; Charlo, H. C O [UNESP]; Ito, L. A. [UNESP]; Braz, L. T. [UNESP] (My University, 2006)
The aim of the work was to evaluate the performance of four cultivars of iceberg lettuce, in a greenhouse, with and without ground cover. The experimental design adopted was that of subdivided parcels, where parcels were provided with and without ground cover consisting of black polyethylene and the subparcels consisted of the cultivars. There were three repetitions per treatment and six central plants of each parcel were evaluated. Drip irrigation was utilized. The cultivars studied were: 'Laurel', 'AF-389', 'Mayara' and 'Tainá'. The seeds were planted in Styrofoam trays with 288 cells containing the substrate Plantmax Hortaliças® A. The trays were kept in a greenhouse until transplanting, 25 days after seeding. The parameters examined were: fresh weight of the aerial part per plant, longitudinal (DL) and transverse (DT) diameters of the head, height of the plant and mean number of leaves per plant. Only among the cultivars there were significant differences in transverse and longitudinal diameters of the head and height of the plant. No significant interactions were detected between ground cover and cultivars. With regard to longitudinal and transverse diameters, 'AF-839' (DL = 27.11 cm; DT = 24.53 cm) showed smaller diameters than those of 'Laurel' (DL = 31.13 cm; DT = 30.55 cm), but did not differ from the other cultivars. In regard to height of the plants, 'Laurel' (20.66 cm) had the greatest value and 'AF-839' (16.02 cm) the lowest. The cultivars did not differ with respect to mean number of leaves and fresh weight of the aerial part of the plant. It is concluded that there were no significant differences in the cultivation of the iceberg lettuce with and without ground cover. The cultivar 'Laurel' stood out with respect to longitudinal and transverse diameters and height of the plant, only differing from the 'AF-839' with regard to the diameters.
Keywords: Lactuca sativa; Productivity; Protected cultivation; Lactuca